PEMANFAATAN MEDIA SOSIAL PUBLIC RELATIONS AGENCY DALAM MEMBANGUN CUSTOMER ENGAGEMENT : Studi Kasus Instagram aeonmallbsdcity - Qaedy Qasthary, - (2019)
Worldwide Communication manages the aeonmallbsdcity Instagram with a wide range of audiences to build customer engagement. This study aims to find out where the stages of customer engagement have been reached by the aeonmallbsdcity Instagram account. The relevant concept in this study is the concept of the stages of customer engagement according to Dave Evans, because the concept of the customer engagement stage proposed by Dave Evans is the stage of customer engagement through social media. This research was conducted using qualitative methods, with a case study method. The collection technique used was in-depth interviews and directly with Senior Public Relations Worldwide Communications, Content Creators and followers of the aeonmallbsdcity Instagram account. In this study, the results found that the utilization of Instagram media social media in building customer engagement has reached the collaboration stage, which is the highest stage of the customer engagement stage, Dave Evans